Backdoor use of philosophers in judicial decision-making? Antipodean reflections. Issue 3 (2nd July 2016) - Schultz, Karen
ABSTRACT: The citation of philosophers in common law judicial decision-making has been rarely explored. Yet this issue divided two American commentators: Rao, in 1998, critiqued the United States Supreme Court's (USSC) citation of philosophers, labelling it a 'backdoor method for judicial policy making'; Brooks, in 2003, offered a trenchant rejoinder, arguing that philosophy is potentially an 'ally in the pursuit of sensible legal reasoning'. As issues of the curial use of exogenous or extra-legal knowledge are not settled, there is value in reflecting on Australian judicial practice. This article proceeds in three stages. First, it locates Rao's analysis of the USSC's citation of philosophers within a larger picture that concerns issues of citation analysis. Second, it critiques Rao's definitions of philosophy and adjudication in terms of three 'antipodal pairs' of characteristics – pragmatism versus abstraction, institutionalism versus intellectualism, and precedent versus permeability. Third, rejecting Rao's thesis, this article conducts an exploratory survey to consider how the Australian High Court cites the named philosophers in Rao and Brooks's surveys.